Effect Of Particle Geometry On Properties Of Binderless Particleboard From Oil Palm (E/Aeis Guineensis) Trunk - Saari, Norhafizah (2012)
Binderless particleboard panels were manufactured from two different particle geometry of oil palm (E/aeis guineensis) trunk. The types of particle used were fine particles and strands. Strands that were composed of vascular bundles with some parenchyma cells attached together while fine particles were grounded particles with size less than I 000 1-1m. The binderless particleboard panel was manufactured with target density of 0.80 g/cm3 Binderless particleboard panels were tested for their mechanical and physical properties such as modulus of rupture (MOR) or bending strength, internal bond strength (IB), thickness swelling (TS), water absorption (W A) and surface roughness. Chemical analysis such as starch analysis and total sugar analysis were carried out to determine the starch and sugar content in the sample. Besides that, spectroscopic characterization was carried out using Fourier Transform Infrared (FTlR) spectroscopy to detect the functional group presence in the sample for untreated and steam pre-treated samples. Scanning electron microscopy was done to observe the anatomical features of binderless particleboard panels of different type particles using Scanning Electron Microscopy (SEM) from the micrograph taken. Characteristic such as weight changes in relation to temperature was tested by Thermogravimetric (TGA) equipment. TGA can also determine the degradation of binderless particleboard panels. The results showed that binderless particleboard panels made using strands had higher modulus of rupture (MOR) and internal bond (IB) than fine particles binderless particleboard panels which were 0.93 MPa and 24.95 MPa respectively.